Development of Finite Element Model for Charring Rate for Solid Timber from Malaysian Tropical Hardwood Subjected to Standard Fire - Lannie, Francis; Ahmad Beng Hong, Kueh; Norshariza, Mohamad Bhkari; Hafizah, Muhamad Azlan; Zakiah, Ahmad (North Carolina State University, 2025)
Timber has natural fire resistance because of its predictable charring behavior. When subjected to high temperatures, timber undergoes pyrolysis, forming an insulating char layer that protects the inner structural core. Eurocode EN 1995-1-2 (2004), commonly known as Eurocode 5 where EC5 specifies 0.5 mm/min charring rate for temperate hardwoods, pertains to timber with density exceeding 450 kg/m³. This paper presents the development of a finite element model (FEM) to predict the charring rate of timber exposed to fire through innovative experimental and numerical approaches. Timber samples were exposed to controlled heat fluxes for 60 min, simulating real-world fire scenarios. The resulting char layer thickness was measured over time. The Malaysian tropical hardwood timber used was Resak (Cotylelobium and Vatica spp.) with density range from 932 kg/m3 to 1125 kg/m3. The proposed FEM was developed using ABAQUS software, which included thermal conductivity and specific heat to simulate the transient heat transfer and degradation processes in timber. It was found that the charring rate of Resak was 0.47 mm/min lower than the rates established in EC5 (2004). The model is validated through experimental data, demonstrating its accuracy in predicting char depth and temperature profiles under standard fire condition. The data are useful when designing the fire safety of timber structures from the Malaysian tropical timber species.